Gamifying Student Routines to Improve Campus Experience Through Mobile Application in Indonesia - ., Janssen; Rusli, Andre; Irmina Prasetiyowati, Maria (International Journal of Engineering and Technology, 2018)
Smart campus is an emerging concept in recent years that enables as a part of the smart city movements which leverages the use of information technology in building a comprehensive and sustainable living environment. Several campuses in Indonesia and abroad have already started the movement and integrate the collegesâ€™ data and provide a digital experience for the campus communities. In order to motivate the communities, in this case the students, to leverage IT tools and platforms to improve their learning experiences, utilizing gamification and mobile technologies are seen to be the suitable combinations. Gamification as a concept to enhance user participation is also gaining a lot of tractions in recent years, including in the higher education sector. Many researches have shown that gamification is effective to improve motivations in core learning activities, to push students to be more proactive in gaining knowledge. This research is conducted to integrate a new mobile application to the existing smart campus platform in Universitas Multimedia Nusantara, Indonesia, while also gamify several student routines and activities to enhance the campus experience. The system is built as a hybrid mobile application and evaluated for its user acceptance by analyzing its usersâ€™ perceived usefulness and perceived ease of use which are derived from the technology acceptance model (TAM). Based on the feedbacks gathered from the users, the gamified system is perceived to be easy to use and useful to increase studentâ€™s participation and to motivate the users to actively complete their campus routines.Â Â Â